2018
DOI: 10.3390/su10010261
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Energy Consumption in Northeast Asia: A Case from China’s Fuel Oil Futures Market

Abstract: The sustainable energy consumption in northeast Asia has a huge impact on regional stability and economic growth, which gives price volatility research in the energy market both theoretical value and practical application. We select China's fuel oil futures market as a research subject and use recurrence interval analysis to investigate the price volatility pattern in different thresholds. We utilize the stretched exponential function to fit the pattern of the recurrence intervals of price fluctuations and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In order to investigate the price volatility pattern in different thresholds, Zhang et al utilized the stretched exponential function to fit the pattern of the recurrence intervals of price fluctuations and found that the probability density functions of recurrence intervals in different thresholds [17]. They utilized a hazard function to introduce the recurrence intervals into the value at risk (VaR) calculation, and concluded that the Chinese government should improve energy futures market construction and promote risk control to enhance the global influence of China's energy futures market [17] (p.11). Here, the prudent regulation is emphasized regarding the fuel oil futures market as well.…”
Section: Regulation Toward Green Technologymentioning
confidence: 99%
“…In order to investigate the price volatility pattern in different thresholds, Zhang et al utilized the stretched exponential function to fit the pattern of the recurrence intervals of price fluctuations and found that the probability density functions of recurrence intervals in different thresholds [17]. They utilized a hazard function to introduce the recurrence intervals into the value at risk (VaR) calculation, and concluded that the Chinese government should improve energy futures market construction and promote risk control to enhance the global influence of China's energy futures market [17] (p.11). Here, the prudent regulation is emphasized regarding the fuel oil futures market as well.…”
Section: Regulation Toward Green Technologymentioning
confidence: 99%
“…The sustainable development of energy has a huge influence on regional stability and economic growth [1]. Governments regulate relevant policies to drive the energy sustainability, but it usually takes a long time from the formulation of a policy to its implementation.…”
Section: Introductionmentioning
confidence: 99%